Properties of Barium Strontium Titanate (Ba1-xSrxTiO3, 0 £ x £ 1) Ceramics Prepared by Hydrothermal Process - Zeng, Min; Fan, Wei (Asian Journal of Chemistry, 2014)
Barium strontium titanate (Ba1-xSrxTiO3, 0 £ x £ 1) was produced in a pressure vessel at 180 °C for 24 h using a facile hydrothermal technique, without any surfactants or templates, with an alkalescency solution. The as-prepared products were characterized by X-ray diffraction, transmission electron microscopy, the differential thermal analysis and thermo-gravimetry analysis and electron diffraction. The barium strontium titanate nanoparticles in various compositions were monodispersed without mutual aggregation and their average sizes were in the range of 50-80 nm. Furthermore, they showed highly crystallized perovskite phase over the whole composition range. The stoichiometry of the (Ba1-xSrx)TiO3 powder is discussed in relation to the mechanism of formation of the perovskite phase.